Modelo hidrológico distribuído unidimensional para bacias hidrográficas peri-urbanas - Souza, Rávila Marques de (2014)
This study aimed to develop and calibrate a distributed hydrological model used for a one-dimensional drainage of a peri-urban catchment using the optimization multi-objective method Non -dominated Sorting Genetic Algorithm (NSGA - II) for model calibration. Computational algorithms developed in MATLAB environment were adopted to make this study possible. This model allows a precipitation event to set the surface runoff hydrograph at any position of the watershed (planes or channels) regarding infiltration effect and soil physical characteristics. Objective functions were defined and used simultaneously to calibrate the model. From sensitivity analysis performed, it was found that the model is more affected by the parameters related to permeable areas. The model fit was very good, illustrating the applicability of multi-objective calibration in exploring ideal area and to obtain ideal solutions. Validation proved the efficiency of the model used for other different rainfall events in Samambaia stream basin, generating outputs with good accuracy and optimal theoretical value results for Nash & Sutcliffe coefficients of efficiency near the area region.